Spatial impact of foreign direct investment on poverty reduction in Vietnam - Do Quynh Anh; Le Quoc Hoi; Nguyen Thanh Duong; Van Anh Vu; Tran Lan Huong; Nguyen Cuc Thi Thu (Journal of Risk and Financial Management, 2021)
In this study, we analyze the spatial effect of foreign direct investment (FDI) on poverty reduction in Vietnam. This study uses the provincial-level panel data and the fixed-effects regression and the spatial econometric model to investigate empirically the impact of FDI on poverty reduction in Vietnam. The study finds that FDI has contributed to poverty reduction not only directly but also indirectly through human capital. However, FDI has indirectly worsened poverty through international trade. In addition, empirical results from the spatial econometric model show that FDI tends to decrease poverty in provinces. Finally, the study has some policy implications to decrease the negative effects of FDI on poverty reduction in Vietnam.
Keywords: F21; F23; O11; C23; I32; 330; foreign direct investment (FDI); poverty reduction; Vietnam